2018
DOI: 10.15561/18189172.2018.0205
|View full text |Cite
|
Sign up to set email alerts
|

Physical health of schoolchildren aged 14-15 years old under the influence of differentiated education

Abstract: Purpose:to determine the dynamics of indicators of schoolchildren physical health under the influence of a multilevel system of differentiated education. Material:The study involved schoolchildren (n = 148, age 14-15 years). Two control groups and two experimental groups were formed. Quantitative assessment of physical health was carried out according to 5 indices. Results:a low level of physical health of schoolchildren is established. The influence of the means of a multilevel system of differentiated educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The range of indices reflecting physical fitness and adaptive capacity was applied to assess the dynamics of physical health under the influence of a multi-level system of differentiated education (Masliak & Mameshina, 2018). Krivoruchko, Masliak, Bala, Skripka and Honcharenko (2018) applied the physical development indices as a criterion for the effectiveness of training in cheerleading.…”
Section: Discussionmentioning
confidence: 99%
“…The range of indices reflecting physical fitness and adaptive capacity was applied to assess the dynamics of physical health under the influence of a multi-level system of differentiated education (Masliak & Mameshina, 2018). Krivoruchko, Masliak, Bala, Skripka and Honcharenko (2018) applied the physical development indices as a criterion for the effectiveness of training in cheerleading.…”
Section: Discussionmentioning
confidence: 99%
“…The above is confirmed by the data of (Adel et al, 2019;Mokhtar et al, 2019;Saddek et al, 2020), according to which it was found that during physical exertion, muscle hypertrophy occurs as a result of adaptive-trophic influence (Mukund & Subramaniam, 2020;Teplov, 1982), which is characterized by an increase in thickness and denser packaging of contractile elements of muscle fiber (Haun et al, 2019;Narici et al, 1996). Thus, studies (Annesi, Westcott, Faigenbaum, & Unruh, 2005;Belkadi et al, 2019;Krivoruchko et al, 2018;I. P. Masliak & Mameshina, 2018) indicate that the introduction of functional exercises in the main part of the lesson contributed to a significant improvement in strength abilities of high school students.…”
Section: Discussionmentioning
confidence: 64%
“…To date, there is a problem of decline level of physical fitness, and as a consequence of health student youth. A number of leading experts (Harold W. Kohl, Cook, Environment, Board, & Medicine, 2013;Kaur, Singh, Arya, & Mittal, 2020;Mameshina, 2019;I. P. Masliak & Mameshina, 2018;Petrova & Bala, 2020) note that according to statistics, almost 60% high school children have health problems and low levels of physical fitness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation